An efficient fluctuating charge model for transition metal complexes. Issue 18 (22nd April 2013) - Comba, Peter; Martin, Bodo; Sanyal, Avik
<x xml:space="preserve">Abstract</x> A fluctuating charge model for transition metal complexes, based on the Hirshfeld partitioning scheme, spectroscopic energy data from the NIST Atomic Spectroscopy Database and the electronegativity equalization approach, has been developed and parameterized for organic ligands and their high‐ and low‐spin FeII and FeIII, low‐spin CoIII and CuII complexes, using atom types defined in the Momec force field. Based on large training sets comprising a variety of transition metal complexes, a general parameter set has been developed and independently validated which allows the efficient computation of geometry‐dependent charge distributions in the field of transition metal coordination compounds. © 2013 Wiley Periodicals, Inc.